Workplace bullying, personality and work engagement among South African employees - Omar, Tasneem (My University, 2017)
Workplace bullying is an unfortunate occurrence within organisations and has become a prevalent area of interest. However, research on workplace bullying and specifically its effect on work engagement within a South African context is rare. Additionally, research on the relationship between workplace bullying and personality traits is limited to the Big Five personality traits. This research thus broadened its range from the Big Five personality traits and focused on neuroticism, assertiveness, optimism, pessimism and hardiness. The research further assessed the moderating effect of personality on the relationship between workplace bullying and work engagement. The sample consisted of 200 white collar employees over the age of 18 that was obtained using a volunteer, snowball sampling method. The responses were obtained using survey methodology, which led to the cross-sectional nature of the study. Analyses of results were completed using a Pearson’s product moment correlation analysis and a moderated multiple regression analysis. The results from the Pearson’s product moment correlation mainly supported the hypotheses, however there were findings that countered the hypotheses, mainly assertiveness as this proved to be the most unexpected finding. The results from the moderated multiple regression showed that only neuroticism and pessimism moderated the relationship between workplace bullying and work engagement as opposed to assertiveness, optimism and hardiness that did not. The findings of this research thus contribute to the limited body of South African research investigating different personality types moderating the relationship between workplace bullying and work engagement.
A research project submitted in partial fulfilment of the requirements for the degree of MA by coursework and Research Report in the field of Industrial Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg July 2017
Keywords: Bullying in the workplace--South Africa; Organizational behaviour--South Africa; Psychology, Industrial--South Africa